A proposal for replicating Evanschitzky, Baumgarth, Hubbard, and Armstrong's "Replication research's disturbing trend" (Journal of Business Research, 2007) - Raymond Hubbard (Kiel Institute for the World Economy (IfW), 2017)
This paper is about how the author proposes to replicate Evanschitzky, Baumgarth, Hubbard, and Armstrong's "Replication research's disturbing trend" (Journal of Business Research, 2007). This is because estimating the incidence of published replication research and its outcomes must be continued.
Keywords: A14; B23; B41; C18; 330; eplication; replication with extension; statistical power analysis; overlapping confidence intervals